The “New” Beckett and the Word/Image Parallax: An Infra-Disciplinary Short-Circuit - Robert Kilroy (Sillages Critiques)
This article contributes to the ongoing debate about the paradigmatic shift in Visual Culture by outlining the theoretical parameters of a new approach to the study of text/image relations. In doing so it also builds on the most recent scholarship in Beckett Studies by offering a new theoretical framework for interpreting Beckett’s work. First, the word/image problematic is re-conceptualized through reference to the writings of Slavoj Žižek. On the basis of a “word/image parallax”, a new iconological approach is elucidated by adapting art historical tools in line with psychoanalytic theory. The application of this model as a tool for textual analysis is then epistemologically justified from within the domain of literary criticism. In developing this point, I aim to illuminate the parallax logic of both Beckett’s work and the critical reaction it provokes in order to propose a new direction in scholarship. The broader argument is that the field of Beckett Studies allows for a new type of disciplinary encounter – what I call an “infra-disciplinary” short-circuit – to take place between art history and literary criticism.